2020
DOI: 10.1101/2020.11.17.20232975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leukocyte telomere length in patients with multiple sclerosis and its association with clinical phenotypes

Abstract: Aging is a significant factor influencing the course of multiple sclerosis (MS). Accelerated telomere attrition is an indicator of premature biological aging and a potential contributor to various chronic diseases, including neurological disorders. However, there is currently a lack of studies focusing on telomere lengths in patients with MS.We measured the average leukocyte telomere length (LTL) in biobanked DNA samples of 40 relapsing-remitting MS patients (RRMS), 20 primary progressive MS patients (PPMS) an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…In the studies by Guan et al, the measured TL were on average 26% and 24% shorter in the PPMS subgroup [51] and in the general MS group [52], respectively, as compared to the controls. In line with this, Habib et al found significantly shorter telomeres in each MS subgroup (RRMS: 19%, SPMS: 29% and PPMS: 29% shorter) [55], and, finally, Hecker et al observed 18% shorter LTL in the RRMS patient cohort than in the control cohort [56]. A meta-analysis of these 4 studies substantiated that LTL are significantly shorter in MS patients as compared to healthy controls (overall SMD=−0.66, p=0.003).…”
Section: Comparative Assessment Of Studies On Tl In Msmentioning
confidence: 68%
See 4 more Smart Citations
“…In the studies by Guan et al, the measured TL were on average 26% and 24% shorter in the PPMS subgroup [51] and in the general MS group [52], respectively, as compared to the controls. In line with this, Habib et al found significantly shorter telomeres in each MS subgroup (RRMS: 19%, SPMS: 29% and PPMS: 29% shorter) [55], and, finally, Hecker et al observed 18% shorter LTL in the RRMS patient cohort than in the control cohort [56]. A meta-analysis of these 4 studies substantiated that LTL are significantly shorter in MS patients as compared to healthy controls (overall SMD=−0.66, p=0.003).…”
Section: Comparative Assessment Of Studies On Tl In Msmentioning
confidence: 68%
“…Subsequently, 18 studies were discarded because they did not contain an analysis of MS patient samples (III), and finally, 21 studies were rejected because they were not concerned with measuring TL (IV). In consequence, we included 7 studies in our systematic review [50][51][52][53][54][55][56] (Supplemental Table 1). Four of these studies also provided sufficient data to be pooled into a meta-analysis [51,52,55,56].…”
Section: Search Results Study Selection and Overviewmentioning
confidence: 99%
See 3 more Smart Citations